2019
DOI: 10.1016/j.jtho.2018.09.022
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Minimal Residual Disease Using ctDNA in Lung Cancer: Current Evidence and Future Directions

Abstract: Advances in DNA sequencing methods have significantly expanded the potential clinical applications of analyzing circulating tumor DNA (ctDNA). This genetic information can identify the presence of targetable mutations and has been explored for cancer screening purposes. ctDNA can be obtained without the risks inherent to biopsy, allowing for serial assessments over time. Several studies have additionally suggested that ctDNA can be used to detect the presence of minimal residual disease (MRD) after surgical re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
79
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 113 publications
(79 citation statements)
references
References 75 publications
0
79
0
Order By: Relevance
“…Similarly, following surgery ctDNA levels are known to plummet within 1 day [36]. Levels immediately postsurgery can indicate minimal residual disease detection, which may guide the clinical management [37]. Radiological relapse post-surgery has been predicted by ctDNA increases up to 5.2 months prior [38].…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, following surgery ctDNA levels are known to plummet within 1 day [36]. Levels immediately postsurgery can indicate minimal residual disease detection, which may guide the clinical management [37]. Radiological relapse post-surgery has been predicted by ctDNA increases up to 5.2 months prior [38].…”
Section: Discussionmentioning
confidence: 99%
“…The genomic coverage (i.e., targeting specific genomic alterations versus broader panels of genes or a combination of these approaches) should also be considered when choosing a ctDNA assay [22]. ctDNA genotyping can be targeted to known mutations in predefined genes or non-targeted and aim at whole exome screening (discussed below) [41]. Targeted approaches are generally more sensitive than non-targeted assays; however, ultrasensitive technologies have been described [19].…”
Section: Analytical Aspects and Methods Of Ctdna Analysismentioning
confidence: 99%
“…For patients with advanced disease, ctDNA test results appear more reliable when performed at disease progression rather than during response to therapy [32]. This implies that confirmation of ctDNA negative tests is still recommended using tumor biopsy [1,41,49]. At the other end, false-positive findings can be introduced due to the presence of cfDNA from multiple sources, including age-related mutations from hematopoietic cells that and ctDNA mutations that are shared between cancer and benign conditions [41].…”
Section: Liquid Versus Tissue Biopsiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, studies have demonstrated that ctDNA can be used to detect minimal residual disease (MRD) after surgical resection and, therefore, identify patients at an increased risk of disease recurrence ahead of standard-of-care imaging surveillance [ 85 ]. With the recent data from the TRACERx (tracking non-small-cell lung cancer evolution through therapy (Rx)) study available, independent predictors of ctDNA release and phylogenetic ctDNA tracking provided insights into the subclonal nature of lung cancer relapse and metastasis [ 86 ].…”
Section: Evolving Role Of Liquid Biopsy In Nsclcmentioning
confidence: 99%